PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DIREKTORAT PENGELOLAAN LAHAN - Nidel, Muhammad Ihsan; Suhardi, Adnan (Universitas Batam, 2021)
Influence of organizational culture, leadership style, and communication on employee performance of BP Batam Land Management Directorate This study aims to examine and analyze the influence of organizational culture, leadership style, and communication on employee performance of BP Batam Land Management Directorate. Data was collected through questionnaires distributed to 145 employees. The analysis in this study uses the SPSS version 22 program. The data testing technique used is validation test and reliability test with Cronbach Alpha. From the results of the coefficient of determination (R2), it can be seen that employee performance is influenced by compensation, organizational culture, leadership style, and communication by 0.227 (22.7%), while the remaining 77.3% is influenced by other factors that do not support this research.